Turismo e comunicação : a festa da colônia em Gramado-RS sob o olhar da imprensa - Meneghel, Lirian Maria (My University, 2016)
Colonia’s party had originated in 1984, when a group of residents of Linha Bonita, in Gramado / RS, proposed the holding of a festive time for the local community. Soon the party grew and gained identity, starting to be held in the Center City of Gramado and today is one of the major tourist events in the city. This research had as objective strengthen the rapprochement between communication and tourism, investigating how the print media disseminates the Colonia’s party of Gramado/RS. The corpus of the research was delimited to the newspapers Zero Hora, Pioneiro, Integração and Gramado, using the methodology of content analysis as proposal by Laurence Bardin. The results showed that the newspapers are partners in the disclosure of the aspects that make the party attractive and attended, as they are also the promoters of gastronomy, culture and leisure, valuing the participants, whether visitors, promoters and/or organizers as well as the supporting elements, products and commercialization.
A festa da Colônia teve sua origem em 1984, quando um grupo de moradores da Linha Bonita, em Gramado/RS, propôs a realização de um momento festivo para a comunidade local. Logo a festa cresceu e ganhou identidade, passando a ser realizada no Centro de Gramado, sendo hoje um dos principais eventos turísticos da cidade. A presente pesquisa teve como objetivo reforçar a aproximação entre a comunicação e o turismo, investigando como a mídia impressa divulga a Festa da Colônia de Gramado/RS. O corpus da pesquisa delimitou-se aos jornais Zero Hora, Pioneiro, Integração e de Gramado, utilizando-se como metodologia a Análise de Conteúdo conforme proposta de Laurence Bardin. Os resultados revelaram que os jornais são parceiros na divulgação dos principais aspectos que tornam a festa atrativa e frequentada, como também são os promotores dos elementos gastronomia, cultura e lazer, valorizando os participantes, quer sejam visitantes, promotores e/ou organizadores, bem como os elementos coadjuvantes, produtos e comercialização.
Keywords: Turismo - Gramado (RS); Turismo cultural; Comunicação; Imprensa; Festas folclóricas; Tourist trade - Gramado (Brazil); Heritage tourism; Communication; Press; Folk festivals